Features of affairs on bankruptcy, their place in a civil procedural law (Journal of actual problems of jurisprudence, 2019)
In article problem questions of legal proceedings on cases of bankruptcy, their place in a civil procedural law ofthe Republic of Kazakhstan regarding a ratio of bankruptcy of individual entrepreneurs and the legal entities, theaccelerated rehabilitation and rehabilitation of legal entities to a special type of production are considered. Also inarticle legal proceedings questions on cases of bankruptcy on the basis of achievements of science of a civil procedurallaw are considered.Key words: bankruptcy, insolvency, bankruptcy of individual entrepreneurs and legal entities.